Acid resistance of palm oil fuel ash and metakaolin ternary blend cement mortar - Usman, J. (Chinese Institute of Environmental Engineering, 2017)
This paper examines the effects of blend of Palm Oil fuel ash (POFA) and Metakaolin (MK) on the resistance of cement mortar to sulphuric acid (H2SO4) attack. Tests were conducted on POFA and MK ternary blended cement mortar immersed in a 3% H2SO4 solution for up 180 d. Binaries of POFA/cement and MK/cement as well as plain ordinary Portland cement (OPC) mortar was also tested for comparison. The parameters measured include residual compressive strength and residual mass. Additionally, the microstructures of the specimens were analysed using the X-ray diffraction and Fourier transformed infrared techniques. The residual compressive strengths of the mortar specimens for plain OPC, binary blend of POFA and cement, binary blend of MK and cement, and ternary blend of POFA, MK and cement after 180 d of immersion in the acid solution were 25, 30, 33, and 32%, respectively. Moreover, the corresponding residual masses of the specimens were 39, 52, 58, and 54%. Accordingly, the ternary blended mortar performed better in resisting H2SO4 attack than the plain OPC and binary blend of POFA/cement mortars.